Manajemen Pemenuhan Fasilitas Pendidikan di SMK As-Sulaimaniyyah Kabupaten Cianjur Provinsi Jawa Barat - Agus Ruswandi; Aang Mahyani; Mohamad Erihadiana (Jurnal Bahana Manajemen Pendidikan, 2021)
The purpose of this study was to describe the planning, organization and implementation monitoring the fulfillment of facilities and maintenance of educational facilities at SMK As Sulaimaniyyah Cianjur Regency, West Java. The research method is a naturalistic descriptive research method through a qualitative approach with interview and documentation data collection. The results of this research indicate that schools carry out facility management planning by making specific, general, short and long-term work programs. The draft work program is submitted to the principal for discussed with the committee, foundation and parents of students. Once approved, then determine the design for the procurement and maintenance of facilities and infrastructure in the form of an estimate for the procurement of a full academic periode. The organization and implementation of the fulfillment of facilities at SMK As-Sulaimaniyyah is carried out at least in 6 stages. The school determines the source of funds, ensures the availability of sources, determines the allocation of funds and the amount, procurement of goods or services both for facilities that do not yet exist and for the maintenance of existing facilities. Conduct an inventory of existing or newly provided facilities, and carry out maintenance of facilities in schools. Supervision of the management of facilities and infrastructure is carried out by internal and external parties. Internal parties supervise all procurement of facilities, while external parties only supervise facilities originating from BOS funds. With the current conditions, this insitution schools can meet about 60% of the standard facilities set by government regulations